Matched Comparison of Self-Expanding Transcatheter Heart Valves for the Treatment of Failed Aortic Surgical Bioprosthesis: Insights From the Valve-in-Valve International Data Registry (VIVID). (April 2017) - Alnasser, Sami; Cheema, Asim N.; Simonato, Matheus; Barbanti, Marco; Edwards, Jeremy; Kornowski, Ran; Horlick, Eric; Wijeysundera, Harindra C.; Testa, Luca; Bedogni, Francesco; Amrane, Hafid; Walther, Thomas; et al.
Abstract : Background—: Transcatheter valve-in-valve implantation is an established therapy for high-risk patients with failed surgical aortic bioprosthesis. There are limited data comparing outcomes of valve-in-valve implantation using different transcatheter heart valves (THV). Methods and Results—: Patients included in the Valve-in-Valve International Data registry (VIVID) and treated with self-expanding THV devices were analyzed using centralized core laboratory blinded to clinical events. St. Jude Medical Portico versus Medtronic CoreValve were compared in a 1:2 fashion after propensity score matching. A total of 162 patients, Portico- (n=54) and CoreValve- (n=108) based valve-in-valve procedures comprised the study population with no significant difference in baseline characteristics (age, 79±8.2 years; 60% women; mean STS [Society of Thoracic Surgery] score 8.1±5.5%). Postimplantation, CoreValve was associated with a larger effective orifice area (1.67 versus 1.31 cm 2 ; P =0.001), lower mean gradient (14±7.5 versus 17±7.5 mm Hg; P =0.02), and lower core laboratory–adjudicated moderate-to-severe aortic insufficiency (4.2% versus 13.7%; P =0.04), compared with Portico. Procedural complications including THV malpositioning, second THV requirement, or coronary obstruction were not significantly different between the 2 groups. Survival and stroke rates at 30 days were similar, but overall mortality at 1 year was higher among patients treated with Portico compared with CoreValve (22.6% versus 9.1%; P =0.03). Conclusions—: In this first matched comparison of THVs for valve-in-valve implantations, Portico and CoreValve demonstrated differences in postprocedural hemodynamics and long-term clinical outcomes. Although this could be related to THV design characteristics, the impact of other procedural factors cannot be excluded and require further evaluation.